Worsening of the skin diseases’ severity during SARS-CoV-2 pandemic is confirmed irrespective of the leading immune response pattern - Maria K. Monaenkova; Elizaveta D. Abalukhova; Dmitriy Е. Zlobin; Anton V. Molochkov; Мarina А. Gureeva; Oleg V. Karzanov; Yulia V. Molochkova (Alʹmanah Kliničeskoj Mediciny)
Background: The SARS-CoV-2 pandemic can be considered a multifactorial event involving both the direct impact of the virus on the human body and a complex impact (through social, psychological, occupational, and behavioral changes) on the pathomorphosis of many diseases, including skin disorders. The analysis of the incidence, severity, and effectiveness of standard treatments for dermatoses in the new environmental model could be of value for the understanding of the mechanisms of skin disorders, improvement of the approaches to their treatment, development of rehabilitation and preventive tools.